Role of Physio Biochemical Markers of Acute Myocardial Infarction in Young Adults - Aamir Abbas Mughal, Tayyaba Batool, Saadia Zainab, Saima Rubab Khan, Junaid Iqbal, Saima Mukhtar (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Background: Universally, cardiovascular problems remains a major cause of unfavorable results in young individuals, unlike its decrease in other age bunches. This group isn't well studied and includes an interesting hazard profile with less conventional cardiovascular risk components compared with more seasoned populations. Objective: To highlight the prevalence and risk factors of myocardial infarction in young individuals Material and Methods Study design: quantitative cross sectional Settings: Punjab Institute of Cardiology (PIC) Duration: Six months i.e. 1st July2021 to 31st December 2021 Data Collection procedure: A cross sectional study was conducted with the duration of six months in a tertiary care hospital Lahore. Young hospitalized patients were selected with the age limit of 40 years and admitted to hospital with acute myocardial infarction. Total number of patients was 100 placed in the group one and same numbers of individuals with same age group were also selected without history of any cardiovascular diseases from the population as control. Validated Hamilton anxiety rating scale was used to access the anxiety levels of an individual. BMI, cardiac serum markers and liver enzymes were calculated. For this purpose venous blood was obtained from each individual and test was performed. Results: The average age of the participant in this study was in between 20-40 years of age. In group one 77 were males and 23 females. Group two consist of 82 males and 18 females. As we see in the table 1 findings the levels of LDH, trop I, CKMB and SGOT are significantly high in group 1 which showing myocardial injury as the release of these markers in blood. Anxiety levels and cigarette smoking also noticed high in group 1 as compared to group 2. Conclusion: This study illustrated uneasiness as a possibly driving hazard figure of AMI in young individuals, requiring the need for superior administration of psychosocial wellbeing in youthful age for relieving the hazard of AMI. Preventive intercessions are more likely to abdicate useful results in young individuals and future work on such preventive procedures may empower definition of worldwide arrangements and community campaigns to decrease the health-economic burden of AMI in young grown-ups and make strides results of wellbeing and quality of life